2023
DOI: 10.1002/adma.202209912
|View full text |Cite
|
Sign up to set email alerts
|

Reprocessable and Chemically Recyclable Hard Vitrimers Based on Liquid‐Crystalline Epoxides

Abstract: The rapid increase in demand for recyclable and reusable thermosets has necessitated the development of materials with chemical structures that exhibit these features. Thus, functional mesogenic epoxide monomers bearing both ester and imine groups that can be vitrimerized and recycled are reported herein. The compounds show mesophase characteristics at 100–200 °C and can be converted into hard epoxides by a common curing reaction. The obtained hard epoxides have high isotropic thermal conductivity (≈0.64 W m−1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Thus, high-value utilization of throwaway waste material is of great importance for the sustainable development of the society. 5–10…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, high-value utilization of throwaway waste material is of great importance for the sustainable development of the society. 5–10…”
Section: Introductionmentioning
confidence: 99%
“…Thus, high-value utilization of throwaway waste material is of great importance for the sustainable development of the society. [5][6][7][8][9][10] Chewed gum features flexibility, viscosity, and biocompatibility, which promise great potential in stretchable and flexible electronics. 11 For instance, an elastic, attachable, and costefficient chewing-gum-based sensor fabricated by introducing aligned carbon nanotubes (CNTs) into chewing gum through multiple stretching and folding steps could sense strain up to 530% with high sensitivity and durability, thus demonstrating capability for monitoring body movements and tracing slow breathing efficiently.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Reversible bonds that drive self-healing can be broadly categorized into dynamic covalent and non-covalent bonds. Borate ester, [22][23][24] disulde, [25][26][27][28] imine, [29][30][31] acylhydrazone, 32,33 and Diels-Alder 34,35 reactions represent the dynamic covalent bonds employed in self-healing polymers. Among these, the introduction of aromatic groups reduces the activation energy, enabling functionality at room temperature, as demonstrated in a previous study utilizing aromatic disuldes.…”
Section: Introductionmentioning
confidence: 99%
“…12−26 Compared with traditional thermosets, the disposal method of chemically recyclable thermosets is environmentally friendly. 5,6,12,14,21,27,28 To create chemically recyclable thermosets, various cleavable or dynamic covalent bonds such as dynamic imine bonds, 15,[17][18][19]27,29,30 transesterification, 20,22,31 and boroxines 21,23,24 have been decorated on the polymer backbones as cleavable units. For example, Mecking and co-workers reported that polyethylene-like polymers containing the in-chain functional groups as break points can be chemically recycled under heating in a basic ethanol solution at 120 °C.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Plastics are indispensable in our daily life and most technology fields, which drive the mass production of plastic products in the past decades. As one of the most used plastics, thermosetting plastics have accounted for 18% of the total polymers and the worldwide annual production of more than 65 million tons during 2010–2015. However, only a small fraction of thermosetting plastics are disposed in terms of circular economy manner after their service life due to their permanent covalently cross-linking structures. ,,, Therefore, it is of critical urgency to develop new sustainable thermosetting plastics. Chemically recyclable thermosets as a new kind of alternative have shown great potential due to their capability to be degraded to their corresponding precursors or building blocks. Compared with traditional thermosets, the disposal method of chemically recyclable thermosets is environmentally friendly. ,,,,,, To create chemically recyclable thermosets, various cleavable or dynamic covalent bonds such as dynamic imine bonds, , ,,, transesterification, ,, and boroxines ,, have been decorated on the polymer backbones as cleavable units. For example, Mecking and co-workers reported that polyethylene-like polymers containing the in-chain functional groups as break points can be chemically recycled under heating in a basic ethanol solution at 120 °C .…”
Section: Introductionmentioning
confidence: 99%